information technology innovativeness: the roles of management supports, information technology readiness and government's strategy in Palestine public sector - Lubbad, Anas R. M. (2017)
Information technology innovativeness has great potential to extend an ordinary organization’s competency and efficiency, and this applies to governmental intuitions in particular. As such, Palestine has an objective to increase the diffusion of technology. Despite extensive government efforts, the adoption of innovativeness in the information technology sector is still limited. Consequently, there have been extensive efforts to better understand the phenomenon. However, literature review regarding the determinants of innovativeness are not altogether consistent. To provide more insight, this study aimed to develop a research model utilizing the organizational context framework to identify the determinants of the government’s propensity to adopt information technology innovativeness. Since information technology innovativeness is an inter-organizational phenomenon supporting transactions of organizations and institutions, this study emphasizes the context of cultural characteristics. Grounded in inter-organizational theories, this study hypothesized that organizational culture had a moderating role in organizational motivating factors. A total of 500 questionnaires were distributed online by Google Forms to the managers in 21 ministries in the local government in the Gaza Strip. The responses were analysed using the partial least squares approach. The results revealed that government strategy has an insignificant effect on government information technology innovativeness; however, management support and IT readiness have a positively significant effect. Moreover, the results showed that the moderating organizational culture was pronounced. Meanwhile, the moderating role was partially unsupported. These findings demonstrate how the organizational culture in governmental institutions may change the innovativeness motivations. It was importance of considering the views of the governmental institutions for the innovativeness to be done successfully.